Value for money in energy efficiency retrofits in Ireland: Grant provider and grant recipients - Matthew Collins; John Curtis (The Economic and Social Research Institute (ESRI), 2016)
The Sustainable Energy Authority of Ireland (SEAI) administers the Better Energy Homes (BEH) scheme to provide a financial incentive for home owners to engage in energy efficiency retrofits. This study analyses the BEH data and Building Energy Rating data for BEH-participant homes to examine the value for money achieved by households. In addition, this research identifies which retrofit combinations provide greatest value for money, in terms of energy efficiency gains, for the grant provider. We utilise an error-in-variables approach to model the variation in benefits accruing to households of varying characteristics. We find that household and grant provider surplus can be maximised in the short term by retrofitting less energy efficient and larger homes, timber or steel frame homes and houses rather and apartments. The types of retrofits leading to the greatest surplus for both households and the grant provider include cavity wall insulation paired with either a boiler with heating controls or heating controls only retrofit.
Keywords: Q48; D12; 330; Residential energy efficiency retrofit; energy efficient investment; error-in-variables regression